1975
DOI: 10.1126/science.1166301
|View full text |Cite
|
Sign up to set email alerts
|

Speech Perception by the Chinchilla: Voiced-Voiceless Distinction in Alveolar Plosive Consonants

Abstract: Four chinchillas were trained to respond differently to /t/ and /d/ consonant-vowel syllables produced by four talkers in three vowel contexts. This training generalized to novel instances, including synthetically produced /da/ and /ta/ (voice-on-set times of 0 and +80 milliseconds, respectively). In a second experiment, synthetic stimuli with voice-onset times between 0 and +80 milliseconds were presented for identification. The form of the labeling functions and the "phonetic boundaries" for chinchillas and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
307
1
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 629 publications
(320 citation statements)
references
References 9 publications
11
307
1
1
Order By: Relevance
“…An example is the claim that the distinction between voiced and voiceless stops-normally cued by a complex of acoustic differences caused by differences in the phonetic variable known as voice-onset-time-depends on an auditory discontinuity in sensitivity to temporal relations among components of the signal (Kuhl & Miller, 1975;Pisoni, 1977). Another is the suggestion that the boundary between fricative and affricate on a rise-time continuum is the same as the rise-time boundary in the analogous nonspeech case-that is, the boundary that separates the nonspeech percepts 'pluck' and 'bow' (Cutting & Rosner, 1974; but see Rosen & Howell, 1981).…”
Section: Auditory Theories and The Accounts They Providementioning
confidence: 99%
See 1 more Smart Citation
“…An example is the claim that the distinction between voiced and voiceless stops-normally cued by a complex of acoustic differences caused by differences in the phonetic variable known as voice-onset-time-depends on an auditory discontinuity in sensitivity to temporal relations among components of the signal (Kuhl & Miller, 1975;Pisoni, 1977). Another is the suggestion that the boundary between fricative and affricate on a rise-time continuum is the same as the rise-time boundary in the analogous nonspeech case-that is, the boundary that separates the nonspeech percepts 'pluck' and 'bow' (Cutting & Rosner, 1974; but see Rosen & Howell, 1981).…”
Section: Auditory Theories and The Accounts They Providementioning
confidence: 99%
“…[pa]) referred to earlier, which is cued in part by a difference in time of onset of the several formants, and which has therefore been said by some to rest on a general auditory ability to perceive temporal disparity as such (Kuhl & Miller, 1975;Pisoni, 1977). We believe, to the contrary, that the temporal disparity is only the proximal occasion for the unmediated perception of voicing, a distal gesture represented at the level of articulation by the relative timing of vocaltract opening and start of laryngeal vibration (Lisker & Abramson, 1964).…”
Section: How the Motor Theory Makes Speech Perception Like Other Specmentioning
confidence: 99%
“…Is it thanks to general auditory mechanisms or thanks to specialized speech decoding processes? Because some animals, such as chinchillas (Kuhl and Miller, 1975) or quails (Kluender et al, 1987), can be taught to discriminate speech sounds much as humans do (i.e., categorically), some authors claim that phonemes are processed by general psychoacoustic mechanisms and that the properties of phoneme perception are essentially dependent on the physiological properties of the auditory system (Kluender and Greenberg, 1989;Stevens and Blumstein, 1981). Others have provided empirical arguments (e.g., the phenomenon of duplex perception) favoring a specialized speech processor (Liberman and Mattingly, 1989;Liberman et al, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysical evaluations of the perception of specific speech features in animals have been reported for various conditioning/training procedures (e.g., Kuhl and Miller 1975, using the chinchilla; Padden 1982, 1983, monkey;Baru 1975, dog;and Dewson 1964, cat). It was found that animals discriminate many speech-like features in a similar fashion as humans.…”
Section: Introductionmentioning
confidence: 99%